2021
DOI: 10.1186/s13287-021-02202-2
|View full text |Cite
|
Sign up to set email alerts
|

Silencing Smad7 potentiates BMP2-induced chondrogenic differentiation and inhibits endochondral ossification in human synovial-derived mesenchymal stromal cells

Abstract: Background Bone morphogenetic protein 2 (BMP2) is a promising chondrogenic growth factor for cartilage tissue-engineering, but it also induces robust endochondral ossification. Human synovial-derived mesenchymal stromal cells (hSMSCs) have attracted great interest due to their poor potential for differentiation into osteogenic lineages. Smad7 plays a significant in the endochondral ossification. In this study, we explored a new method to amplify the BMP2-induced chondrogenic differentiation of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 49 publications
(76 reference statements)
0
22
0
Order By: Relevance
“…Results show that SCRG1 positively regulated the expression of chondrogenic genes, including SOX9 , COL2A1 , and ACAN , similar to previous research [ 9 , 25 ], indicating that SCRG1 promoted chondrogenic differentiation of UCMSCs in vitro . Chondrogenic and osteogenic differentiation occurs in opposite directions in stem cells [ 26 , 27 ]. Various transcription factors, such as Wnt10b, SOX9, and RUNX2 [ 22 , 28 , 29 ], are upregulated or downregulated to determine the cell fate of MSCs during chondrogenic and osteogenic differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Results show that SCRG1 positively regulated the expression of chondrogenic genes, including SOX9 , COL2A1 , and ACAN , similar to previous research [ 9 , 25 ], indicating that SCRG1 promoted chondrogenic differentiation of UCMSCs in vitro . Chondrogenic and osteogenic differentiation occurs in opposite directions in stem cells [ 26 , 27 ]. Various transcription factors, such as Wnt10b, SOX9, and RUNX2 [ 22 , 28 , 29 ], are upregulated or downregulated to determine the cell fate of MSCs during chondrogenic and osteogenic differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that BMP2-induced high expression of Smad7 serves as the key inhibitor of chondrogenic differentiation [32,34]. In addition, the hypertrophic differentiation of chondrocytes, marked with COL10A1 [15,35], was caused by Smad7, at least in part, during chondrogenic differentiation [15]. Further research revealed that Smad7 inhibited the formation of cartilaginous tissue induced by BMP2 by suppressing the P38 and Smad1/5/8 pathways [32,36].…”
Section: Discussionmentioning
confidence: 94%
“…This molecule plays an important role in the production and protection of the extracellular matrix of articular cartilage [10][11][12][13]. A previous study by our team showed that overexpression of Sox9 enhances BMP-2-induced chondrogenic differentiation in MSCs by downregulating Smad7 expression [14][15][16]. However, the underlying mechanism of how Sox9 regulates Smad7 is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…With biocompatibility, PPCNg has been reported to mediate BMP9-transduced MSCs, including iMEFs [29], iMADs [30] and iCALs [31], which were located at bone defect sites to enhance bone formation and angiogenesis. A recent study has shown that PPCNg combined with hSMSCs transplantation can effectively promote chondrogenic differentiation of hSMSCs by improving nutrient supply at the injured site and providing regular space for cell growth [32].…”
Section: Introductionmentioning
confidence: 99%